Peningkatan Cara Membaca Al- Qur’an Sesuai Dengan Hukum Ilmu Tajwid Dan Makhrajul Huruf - Aulia Ahmad Harahap; Randa Putra Kasea Sinaga (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2023)
The holy book Al-Qur'an belongs to the fourth and last book revealed by Allah SWT to His last messenger, namely the Prophet Muhammad SAW. The Al-Qur'an was revealed with the aim of being a life guide for Muslims, because all the laws and provisions have been regulated and explained in the Al-Qur'an. It is an obligation for us as Muslims to study and understand further matters related to the Al-Qur'an, namely including reading the Al-Qur'an properly and correctly or can be called tartil along with knowing and understanding. Reading the Qur'an is one of the noble practices. Before reading the Koran, it would be better for us to study makhraj and tajwid well so that we will be able to read the Qur’an fluently, properly and correctly. This community service activity has the aim of providing assistance in reading the Qur'an with the correct recitation and the makhraj of the letters.Where in this case the target of this community service activity is devoted to people who do not understand how to read the Qur’an with good and correct recitation and makhraj. The achievement that is expected from the implementation of this activity is the emergence of awareness in society of how important the knowledge of recitation and makhraj letters is in reading the Qur’an.